Lincoln, Neb., Rev. Ordinances pt. 2, ch. 14, art. 16, §§ 1-8 (1895) - (:unkn) unknown (My University, 1895)
It shall be unlawful for any person within said city to carry about the person any concealed pistol, revolver, dirk, bowie knife, billy, sling-shot, metal knuckles, or other dangerous or deadly weapons of any kind, excepting only officers of the law in the discharge of their duties. Also granted the mayor the power to grant licenses
Keywords: CARRY - CONCEALED